2014
DOI: 10.21608/jesaun.2014.115023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of an Adaptive Neuro-Fuzzy Control Scheme for Industrial Robots

Abstract: This paper presents the application of an adaptive fuzzy logic controller with feed-forward component (AFLCF) to the Selective Compliance Assembly Robot Arm (SCARA Robot). The feed forward torque component is computed on-line using an artificial neural network (ANN) which has been trained off-line. This feed-forward component is designed to deliver the ideal torque component to the robot derivers. The feedback fuzzy logic control (FLC) component is made to keep the stability of the closed loop system. As the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Experimental and simulated results show clearly that the fuzzy logic controller gave a better satisfying response than the traditional PID controller in term of minimum overshoot, rise time, settling time, and RMS of tracking error. That main conclusion is in agreement with [41]. Also he observed that the controller gave better performance on joint 2 than joint 1(note: he uses same JUPITER XL SCARA robot ).…”
Section: Simulation Resultssupporting
confidence: 84%
“…Experimental and simulated results show clearly that the fuzzy logic controller gave a better satisfying response than the traditional PID controller in term of minimum overshoot, rise time, settling time, and RMS of tracking error. That main conclusion is in agreement with [41]. Also he observed that the controller gave better performance on joint 2 than joint 1(note: he uses same JUPITER XL SCARA robot ).…”
Section: Simulation Resultssupporting
confidence: 84%